APPLICATION OF THE LISTENING TEAM MODEL ASSISTED BY POWERPOINT MEDIA TO INCREASE LEARNING OUTCOMES AND STUDENT ACTIVITY IN CLASS III SDN BAKARAN KULON 02 - VIVIN ARTANTO (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2021)
ABSTRACT Vivin Artanto, 2021, Application of the Listening Team Model Assisted by Powerpoint Media to Improve Learning Outcomes and Activeness of Class III Students at SDN Bakaran Kulon 02Based on the results of observations at SDN Bakaran Kulon 02, several problems were found in learning in class III which resulted in low learning outcomes and student activity. To improve students' activities and learning outcomes in learning Theme 8 in class III, the researchers applied the Listening Team model with the help of Powerpoint media. The type of this research is classroom action research through Listening Team assisted by Powerpoint media which consists of three cycles. Each cycle consists of two meetings. And each meeting consists of four stages, namely planning, implementation, observation, and reflection. The research subjects were third grade students of SDN Bakaran Kulon 02, Juwana District, Pati Regency. Data collection techniques using tests and non-tests. Data analysis used quantitative descriptive analysis and qualitative descriptive analysis. The results showed that: (1) Student activity in the first cycle obtained an average score of 3.76 in the good category, in the second cycle the average score was 4.04 in the good category and in the third cycle the average score was 4.5 categories. very good. (2) The percentage of classical completeness in the first cycle was 50%, increased in the second cycle to 65%, and increased in the third cycle to 100%. The conclusion of this study is that the Listening Team assisted by Powerpoint media can improve student activities and learning outcomes.Keywords: Listening Team, Media Powerpoint